Can Vitamin E (a-tocopherol) supplementation boost the performances of endurance athletes?
After all, vitamin E is an anti-oxidant' which can protect muscle cell membranes from damage during heavy training. This protection might prevent leakage of key proteins out of muscle fibres after demanding workouts. This lessening of leaking might then enhance recovery from strenuous training sessions and lead to long-term improvements in performance. To determine whether vitamin E might really aid performances, scientists in Freiburg, Germany recently studied 36 racing cyclists from the German men's national team. The cyclists had been cycling competitively for at least seven years.